2020
DOI: 10.21062/mft.2020.090
|View full text |Cite
|
Sign up to set email alerts
|

The influence of parameters of the resistance projection welding of M10 steel nuts to the galvanized steel sheet DP 600 on selected joint characteristics

Abstract: Projection welding belongs to the group of resistance welding technologies. The basic process parameters are the welding current and the current flow time. The resistance projection weldability of the fasteners on metal sheets is not as well understood as the resistance spot weldability of the sheets, so complex studies for the wider application of resistance welding of nuts in the automotive industry are still needed. This research is aimed at valuation the effect of resistance projection welding parameters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Dasar parameter processnya adalah arus listrik dan waktu aliran arus tersebut. Proses pengelasan nut dan baut tidak semudah untuk dipahami jika dibandingkan pengelasan tahanan listrik antara plat dengan pelat sehingga penelitian yang lebih komplek masih tetap dibutuhkan [14] .…”
Section: Faktor-faktor Parameter Pengelasanunclassified
“…Dasar parameter processnya adalah arus listrik dan waktu aliran arus tersebut. Proses pengelasan nut dan baut tidak semudah untuk dipahami jika dibandingkan pengelasan tahanan listrik antara plat dengan pelat sehingga penelitian yang lebih komplek masih tetap dibutuhkan [14] .…”
Section: Faktor-faktor Parameter Pengelasanunclassified
“…For this reason, reducing energy and material losses in methods commonly used in industries is a priority issue. One of the most common methods used in the automotive industry for assembling parts together is projection welding [1,2,3]. There are more than 350 projection welded joints in a vehicle body [4].…”
Section: Introductionmentioning
confidence: 99%
“…Projection welding is performed by the formation of a heat-affected zone (HAZ) on the material being welded by the force exerted by two copper electrodes [5]. This welding technique is a modification of the resistance welding method [2]. Welding current, welding time and electrode strength are important parameters for weld quality in projection welding as in spot welding [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is perfectly applied to copper and copper alloys resistance welding, due to the generally high conductivity of these materials [11]. Recently, many studies on RPW have been reported, including its physical mechanism [10][11][12], parameters optimization [13][14][15][16][17][18][19][20][21][22], microstructure characterization [20][21][22][23][24][25], and numerical process simulation [16,26]. Wehle et al [10] revealed that projection welding can be accounted for in the solid-state welding process, where the intimate weld interface is formed under plastic deformation at elevated temperatures and surface diffusion which enables re-arrangement of the interface to perfectly fit.…”
Section: Introductionmentioning
confidence: 99%